Exploration of Indigenous Molds from Empty Palm Bunch Waste Which Have The Potential As A Cellulose Degradation Agent - Srikandi, Srikandi; Maslahat, Mamay (Sains Natural: Journal of Biology and Chemistry, 2024)
Empty palm oil bunches (TKKS) are waste that has not been utilized optimally by palm oil mills and degraded in nature for a relatively long time. The most significant component in EFB is cellulose, so it needs to be degraded.  This research aims to obtain mold from EFB, which is undergoing decomposition and has the potential to degrade cellulose so that the mold can later be used to break down the cellulose in EFB. The research began by measuring the temperature and pH of the TKKS samples in the middle and upper parts, followed by sampling. The sampling location was at the PTPN III Cikasungka Bogor Palm Oil Factory (PKS), which is located in Mekarjaya village, Cigudeg, Bogor Regency.  The isolation results obtained 19 mold isolates, and then the isolates were grown on carboxymethyl cellulose (CMC) media to test their cellulolytic potential. Microscopic observations of molds that can grow on CMC media are generally thought to be the genus Fusarium sp., Aspergillus sp., Rhizopus sp., Mucor sp., Phanerochaete sp., and Penicillium sp.   The cellulolytic potential test results showed that 18 mold isolates were obtained, three of which were in the high cellulolytic potential category, namely isolates JM313, JM105, and JM518, with cellulolytic indexes of 5.25 respectively, 2.98 and 2.06.